Lecturer Satisfaction Index with Tridharma Services at UIN Walisongo Semarang - Dwimei Ayudewandari Pranatami; Anila Umriana (Journal of Quality Assurance in Islamic Education (JQAIE), 2024)
University as an education provider unit always makes changes to adapt to the times. Lecturers are professional educators and scientists with the main task of transforming, developing, and disseminating science and technology through education, research, and community service. To support the tri dharma task of the lecturer, an assessment and evaluation of the campus's services must be conducted. This study used a survey method with lecturers as the research population. The results of this study showed that lecturer satisfaction in the three aspects tested, namely aspects of education, research, and community service, obtained very high satisfaction index scores.